Hyperthermia-Induced Febrile Seizures Have Moderate and Transient Effects on Spatial Learning in Immature Rats - Nawel Yagoubi; Yosra Jomni; Mohsen Sakly (Behavioural Neurology)
The aim of this study was to characterize a novel animal model hyperthermia-induced febrile seizure and to investigate the impacts of repetitive febrile seizures on spatial learning and memory performances in immature rats. Methods. Rats were subjected to hyperthermia exposure one, two, or three times in 10-day intervals during 30 min in a water bath warmed at 45–50°C and their behaviour was monitored. Morris water maze spatial learning and memory were examined for control and treated groups. Results showed that rats subjected to 30-minute hyperthermia hot water developed rapidly myoclonic jerks and then generalized seizures. After a single hyperthermia exposure, the time for generalised tonic-clonic seizures appearance was 16.08 ± 0.60 min and it decreased gradually with repetitive exposure to reach 12.46 ± 0.39 min by the third exposure. Febrile seizures altered the spatial learning and memory abilities in Morris water maze and increased the time spent to attain the platform after one or two exposures, while after a third exposure rats exhibited the same latency compared to controls. Similar results were obtained in probe test where rats, subjected to hyperthermia for one or two episodes, spent less time in the target quadrant compared to corresponding controls. Further, when platform was moved from northwest to southwest quadrant, memory transfer test indicated that after one or two hyperthermia exposures cognitive performances were slightly altered, while after a third exposure the latency to escape increased significantly compared to untreated group. It was concluded that 30 min of hyperthermia hot water was sufficient to induce febrile seizures in immature rats and an increase of susceptibility was observed with repetitive hyperthermia exposure. Hyperthermia treatment impaired cognitive performances but the effects were mostly transient and moderate.